(untitled) (Journal of the Bangladesh Agricultural University, 2024)
Fish marketing is pivotal in advancing the fisheries sector’s development. The study aimed to explore the marketing dynamics, profit margins and the efficiency of chosen fish species in specific regions of Mymensingh district. The study spanned from October to December 2021, covering various markets within Mymensingh district. Three fish types- Shing, Rui and Pabda, 40 fish farmers, and 152 intermediaries all were chosen purposively. Primary data were gathered through face-to-face interviews. Descriptive statistics, least significant difference, and Shepherd and Acharya methods were employed for analysis. Three marketing channels were identified in the study area, involving fish producers, Aratdar, Aratdar cum wholesaler, Bepari, hawker, retailers, and ultimate consumers. Bepari incurred the highest marketing cost, primarily attributed to transportation costs. Significant differences in marketing costs were observed between Aratdar cum wholesaler (for Pabda and Shing), Bepari with Aratdar, Aratdar with hawker and Aratdar cum wholesaler (for all fish types). The Shing fish exhibited higher profit margin in marketing across intermediaries, except for Bepari. Significant differences in marketing margins were found between Aratdar and Bepari, Aratdar cum wholesaler, hawker and retailer for all three fish types. Retailer marketing margins differed significantly between Rui and Shing fish, Pabda and Rui fish, and Shing and Pabda fish. The Shepherd’s method indicated higher efficiency in marketing in channel 1 compared to channels 2 and 3 for all fish types. Thus, future research should expand to include more diverse geographical areas within Bangladesh to validate and broaden the applicability of these findings, contributing to sustainable growth and profitability in the fisheries sector. J Bangladesh Agril Univ 22(2):210-224, 2024